Perancangan Cangkul Ergonomis Untuk Meningkatkan Kapasitas Kerja Petani dalam Mengolah Tanah Sawah - Wahyu Purwanto (agriTECH, 1992)
Generally, cultivation of rice field in Daerah Istimewa Yogyakarta has been done with hoe. This tool is produced by the small scale industries. Powerlessness of their products lies on many kind of shape and size, because the shape and size of the hoe are decided according to local rice field condition·andbased on the body space of the hoe maker. Variation of shape and size causes man machine system between the farmers and the tools not to be integrated. So, the output of the system will not be optimal. To optimize the output of the system integration between the farmers and the tools is necessary. Design of the ergonomical hoe is to integrate man machine system with anthropometric approach. From an evaluation of 10 kinds of the local hoe and the ergonomical hoe. can be depicted that energy to cultivate rice field is 3.69 kcal/minute and 5.82 kcal/minute for the ergonomical hoe and the local hoe No: 2, respectively. The local hoe No: 2 is classified as bad hoe among 10 kinds of the local hoe. The farmers can cultivate rice field about 54.8 meter square/hour and 44 meter square/hour. if the farmers used the ergonomical hoe and the local hoe No. 2 respectively.This result shows that work productivjty can be increased about 99% by the ergonomical hoe, compared that by the local hoe No: 2. In addition. the body position of the farmers will be natural and working load on the lumbar spinewill be decreased if the ergonomical hoe is used. This condition performs a good·working condition, safety and healthy to the farmers.